2007
DOI: 10.1136/bjsm.2007.043638
|View full text |Cite
|
Sign up to set email alerts
|

Isolated proximal tibiofibular joint dislocation in an elite rugby union player: Figure 1

Abstract: The case is presented of a professional international rugby union player who sustained an isolated proximal tibiofibular dislocation in a training ground injury. Diagnosis was made based on clinical details, plain radiography and magnetic resonance imaging. An initial attempt at closed reduction failed. Open reduction and internal fixation were subsequently carried out. Following early rehabilitation, the patient made a successful try-scoring return to international rugby union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Numerous case reports describe instability of the proximal tibiofibular joint. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Other studies describe specific techniques for ligamentous reconstruction of the proximal tibiofibular joint. [27][28][29][30] However, none of these reports provide detail regarding the anatomic location of the ligaments in association with known surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous case reports describe instability of the proximal tibiofibular joint. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Other studies describe specific techniques for ligamentous reconstruction of the proximal tibiofibular joint. [27][28][29][30] However, none of these reports provide detail regarding the anatomic location of the ligaments in association with known surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
“…MacGiobain et al 8 and Robinson et al 10 also reported a case of open reduction and internal fixation after an initial attempt with closed reduction failed. MacGiobain et al 8 reported the removal of the K wire 6 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most dislocations can be treated through closed reduction; however, open reduction may be required in some cases due to an anterior muscle tension and/or interposition of disrupted capsular ligaments that may resist reduction 9. MacGiobain et al 8 and Robinson et al 10 also reported a case of open reduction and internal fixation after an initial attempt with closed reduction failed. MacGiobain et al 8 reported the removal of the K wire 6 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In the setting of PTFJ injury with intact tibiofibular ligaments, CT imaging can be limited as the subtle anterior migration of the fibula head is not always associated with lateral displacement and thus can lead to misdiagnosis. 10,35 In practice, it appears MRI is rarely required for diagnosis and should not delay definitive management in cases where X-ray and CT findings are suggestive of PTFJ dislocation. 10,35 In practice, it appears MRI is rarely required for diagnosis and should not delay definitive management in cases where X-ray and CT findings are suggestive of PTFJ dislocation.…”
Section: Factors Contributing Towards Ptfj Dislocation Includementioning
confidence: 99%
“…35 Only two cases in the literature progressed to MRI for diagnosis, one following an unsuccessful closed reduction and the other due to the radiation risk of CT in a pregnant patient. 10,35 In practice, it appears MRI is rarely required for diagnosis and should not delay definitive management in cases where X-ray and CT findings are suggestive of PTFJ dislocation.…”
Section: Factors Contributing Towards Ptfj Dislocation Includementioning
confidence: 99%